Construction of Co-NC@Mo2C hetero-interfaces for improving the performance of Li-O2 batteries. (1st April 2023) - Zhang, Lihao; Zhao, Changjiu; Kong, Xianghua; Yu, Shouning; Zhang, Dawei; Liu, Wenhong
Highlights: Mo2 C/Co nano-heterostructures were embedded in the N-doped carbon. The nano-heterostructures synergistically enhance electrochemical performance. Co-NC@Mo2 C was used as Li-O2 batteries (LOBs) cathode catalyst. The LOBs delivers a high discharge capacity and long cycle life. Abstract: Lithium-oxygen batteries (LOBs) are becoming the rising stars of a new generation of energy storage devices due to high theoretical energy density. The crucial factor of its high performance and stability is developing efficient cathode electro-catalysts. In this work, the Zn3 [Co (CN)6 ]2 Prussian Blue analog (Zn-CoPBA) was used as the precursor, then ammonium molybdate tetrahydrate was incorporated by hydrothermal treatment, and finally Mo2 C-modified Co-NC was prepared by one-step pyrolysis. The mesoporous hetero-interfaces of N-doped carbon matrix embedded by Mo2 C/Co nano-heterostructures facilitate the transport of substances, provide more catalytic active sites and storage space for the discharge product Li2 O2 due to the characteristic electronic structure and catalytic properties of Mo2 C with d-orbital state distribution near the noble metal-like Fermi level. The composite Co-NC@Mo2 C was used for LOBs cathode catalyst, it presents wonderful charge-discharge specific capacities (21, 930 mA h g  −   1 ), stable cycling performance. Graphical abstract: In this work, Zn3 [Co (CN)6 ]2 Prussian Blue analog (Zn-CoPBA) was used as the precursor, then ammonium molybdate tetrahydrate was incorporated by hydrothermal treatment, and finally Mo2 C-modified Co-NC was prepared by one-step pyrolysis. The mesoporous hetero-interfaces of N-doped carbon matrix embedded by Mo2 C/Co nano-heterostructures facilitate the transport of substances, provide more catalytic active sites and storage space for the discharge product Li2 O2 . The composite Co-NC@Mo2 C was used for LOBs cathode catalyst, it presents wonderful charge-discharge specific capacities (21, 930 mA h g  −   1 ), stable cycling performance (182 cycles). Image, graphical abstract